Przesłanki decyzyjne kształtowania organizacji sieciowej - Binsztok, Aleksander (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In this article the author shows the possibility of using the conception of the network organisation in the turbulent business environment. Basing on the definition of the network organisation the author presents: - reasons of implementing the organisational solutions, - different forms of network organisations, - what has influence on the structure of the modern companies. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 50-59